2014
DOI: 10.1155/2014/523847
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Shen‐Fu Injection on Neuronal Mitochondrial Function in a Porcine Model of Prolonged Cardiac Arrest

Abstract: Background. Shen-Fu injection (SFI) following cardiac arrest exhibits neurological effects, but its effect on neurological dysfunction is unclear. This study sought to investigate the protective effect of SFI on nerve cells in a porcine model of cardiac arrest. Methods. After eight minutes of untreated ventricular fibrillation (VF) and 2 minutes of basic life support, 24 pigs were randomized and divided into three cardiopulmonary resuscitation groups, which received central venous injection of either Shen-Fu (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Depletion of Δψm will lead to the opening of the MPTP, followed by the release of cytochrome C, apoptosis-inducing factors (AIFs), SMAC/Diablo, and endonuclease G [41,42], which all contribute to mitochondria-mediated apoptosis. Much Suppressive effects of p53 SiRNA on high glucose-induced p53 phosphorylation and caspase-3 activation in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of Δψm will lead to the opening of the MPTP, followed by the release of cytochrome C, apoptosis-inducing factors (AIFs), SMAC/Diablo, and endonuclease G [41,42], which all contribute to mitochondria-mediated apoptosis. Much Suppressive effects of p53 SiRNA on high glucose-induced p53 phosphorylation and caspase-3 activation in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Shenfu has been shown in rats to decrease injury to the central nervous system after cerebral ischemia by decreasing calcium overload, suppressing inflammation, and decreasing apoptosis [ 34 ]. In addition, Shenfu can protect the brain after resuscitation by stabilizing the cellular membrane, suppressing the opening of the mitochondrial permeability transition pore, and alleviating the dysfunction of cerebral mitochondria [ 35 ]. Nevertheless, these mechanistic data are exploratory at best and additional studies are necessary to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia leads to coupling disturbances between brain function and blood flow, glutamate-propagated functional disturbances, free radical mediated changes, disturbances of signaling pathways and gene expression patterns and programmed cell death (Hossmann, 1999). Shenfu injection has been shown to attenuate post-resuscitation cerebral ischemia and reperfusion injury by modulating mitochondrial dysfunction of nerve cells (Gu et al, 2014). Our previous study also showed that shenfu injection protected neonatal hypoxic-ischemic brain injury by preventing neuron apoptosis .…”
Section: Discussionmentioning
confidence: 75%